Correction: Electrochemically shape-controlled synthesis of great stellated dodecahedral Au nanocrystals with high-index facets for nitrogen reduction to ammonia. Issue 81 (1st October 2020) - Jiang, Yu-Chen; Mao, Yu-Jie; Zou, Jin; Wang, Hong-Hui; Liu, Feng; Wei, Yong-Sheng; Sheng, Tian; Zhao, Xin-Sheng; Wei, Lu
Abstract : Correction for 'Electrochemically shape-controlled synthesis of great stellated dodecahedral Au nanocrystals with high-index facets for nitrogen reduction to ammonia' by Yu-Chen Jiang et al., Chem. Commun., 2020, DOI: ; 10.1039/d0cc04326e .